The Impact of Regional Policies on Postpartum Family Planning Services in Special Region Yogyakarta Province : A Run Chart Analysis - Fikriyatul Arifah; Ella Nurlaella Hadi (Universitas Pahlawan Tuanku Tambusai, 2026)
Indonesia’s maternal mortality ratio (MMR) remains high at 189 per 100,000 live births in 2023, far above the 2030 SDG target of 70 per 100,000. One key strategy to reduce MMR is Postpartum Family Planning (PPFP) services, which help prevent closely spaced or unintended pregnancies. The Government of the Special Region of Yogyakarta (DIY) issued Governor Circular Letter No. 11/SE/VII/2022 on PPFP services as a commitment to improving maternal health. This study aimed to describe trends in PPFP coverage in DIY before and after the policy using run chart analysis. A quantitative descriptive design was applied, utilizing secondary data from the Family Information System (SIGA) of BKKBN from January 2022 to December 2023. Run chart analysis was conducted on 24 data points with a median of 820 to detect random and non-random variation based on four rules: shift, trend, runs, and astronomical point. The results showed two major shifts from below to above the median, a six-month upward trend, and only two median crossings, indicating non-random variation. These patterns coincided with the policy’s implementation. In conclusion, a meaningful systemic change in PPFP performance has occurred in DIY since early 2023, suggesting a positive role of regional policy, although causality cannot be confirmed.